Net carbon-di-oxide conversion and other novel features of packed bed biomass gasification with O2/CO2 mixtures. (15th May 2019) - Jaganathan, V.M.; Varunkumar, S.
Abstract: Biomass thermo-chemical conversion under O2 /CO2 conditions is experimentally investigated to establish its CO2 conversion potential. Packed bed configuration with counter-current flame propagation is chosen for this purpose and three different fuels are used (agro-residue pellets, coconut shells and wood pellets). For oxidizer streams containing 20, 25, 30, 40 and 50% O2 (v/v) (rest CO2 ) steady flame propagation is established at different superficial velocities and the following quantities are measured – temperature along the reactor, mass consumption rate and exit gas composition. Corresponding reference experiments with O2 /N2 mixtures are performed for comparing the net CO2 conversion. The propagation regimes, similar to earlier studies with air, fall under the following two categories – (1) gasification – volatile oxidation accompanied by char reduction and (2) char oxidation dominated – simultaneous char and volatile combustion. Invoking equilibration of volatile oxidation under gasification conditions, a new procedure is established to estimate the net CO2 conversion (NCC). In general, NCC is significant around the volatile stoichiometric point ( ϕ v = 1 ) and falls off on either side as the oxygen mass flux is decreased or increased. NCC is zero in very rich regime i.e. when ϕ v ≫ 1 due to low bed temperatures and also when ϕ v < 1 due to char oxidation. Maximum NCC of 627 g/kg of biomass is observed with 30% O2 /70% CO2 (v/v) case at ϕ v = 0.96 for agro residue pellets. Cold gas efficiency ( η g ) is as high as 85% for the maximum NCC case. Enhanced gasification efficiencies of O2 /CO2 cases as compared to corresponding air cases is due to the additional conversion of CO2 to CO (predominantly C + CO2  → 2CO). The difference in the fraction of char left over with CO2 and N2 cases is consistent with this observation. Corrected fuel flux (CFF), proposed to address these variations in fuel heating value, oxygen fraction in the oxidizer etc., is shown to exhibit universality with respect to oxygen mass flux and fuel type.